2010
DOI: 10.1021/ie900614d
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Electrochemical Advanced Oxidation and Electrochemical Hypochlorination of Sulfamethoxazole at a Boron-Doped Diamond Anode

Abstract: Sulfamethoxazole (SMX) was used as a model substrate for electrochemical oxidation at a boron-doped diamond anode in the presence of chloride ion, which is present in many waste streams. In the absence of chloride, oxidation of SMX involves mineralization, an electrochemical advanced oxidation process (EAOP) that is initiated by attack of anode-derived hydroxyl radicals. The rate of disappearance of SMX increased monotonically upon addition of chloride ion but without inhibiting mineralization in the early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…3 to the experimental data. This behavior is often observed during the anodic oxidation of pollutants containing chlorine in its structure or when chloride salts are used as the electrolyte, as hypochlorite is formed at lower electrochemical potentials than other possible oxidants, like persulfate or hydroxyl radicals [51]. Furthermore, the absorbance removal at 275 nm was much low at the lowest current density, but very similar to the removals of COD and TOC for the same applied current density (Fig.…”
Section: Compoundssupporting
confidence: 54%
“…3 to the experimental data. This behavior is often observed during the anodic oxidation of pollutants containing chlorine in its structure or when chloride salts are used as the electrolyte, as hypochlorite is formed at lower electrochemical potentials than other possible oxidants, like persulfate or hydroxyl radicals [51]. Furthermore, the absorbance removal at 275 nm was much low at the lowest current density, but very similar to the removals of COD and TOC for the same applied current density (Fig.…”
Section: Compoundssupporting
confidence: 54%
“…An irreversible oxidation peak of CIP appears before the water discharge at 1 V/SCE. Similar electrochemical behaviour was obtained by Boudreau et al [36] and Karuwan et al [37] in a synthetic solution of SMX and SALBU on a BDD anode, respectively. For both cases, the authors observed the deposition of a polymeric film on the anode, before the water discharge.…”
Section: Determination Of Model Parameterssupporting
confidence: 84%
“…Even more oxidative treatments of wastewaters failed in producing total mineralization [30][31][32][33][34][35][36][37][38], generating unavoidably even more toxic derivatives [28].…”
Section: Introductionmentioning
confidence: 99%